ANALISIS KEAKURATAN REKOMENDASI SAHAM PADA PT RHB SEKURITAS INDONESIA - Rayzi Maulizhar; Fathurrahman Anwar (Departemen Manajemen, 2019)
This study aims to find the accuracy of stocks, target price and bias recommendation by analyzing RHB sekuritas indonesia. The data were collected from primary and secondary. Population of this study were all LQ 45 companies listed in Indonesia Stock Exchange that have been received recommendation from RHB Sekuritas Indonesia for the period of august 2018- january 2019. The hypothesis testing used in this study by using binomial test, the results show that: 1) Accuracy rate of analysis recommendation is 71%. 2) Target price of analysis securities companies doesn't reached.3) Analysis recommendation of pt rhb shown bias negatively.